Extração e caracterização da nanocelulose de fibras mistas de juta (Corchorus capsularis L.) e malva (Urena lobata L.) - Cunha, Claudia Muniz da (BRASIL, 2023)
Nanocellulose is a renewable and biodegradable material obtained from natural sources, which can be applied in the development of numerous new materials, such as polymeric nanocomposites. It can be extracted from numerous raw materials, such as lignocellulosic fibers. In this context, it is understood that the Amazon region has numerous plant species with limited knowledge or in-depth study, which could be reused as a source for nanocellulose extraction. Among these species, jute fiber (Corchorus capsularis L.) and mallow fiber (Urena lobata L.) can be mentioned. With this, the present work aims to perform the extraction and characterization of nanocellulose from these two species. The isolation of nanocellulose was carried out chemically through acid hydrolysis with sulfuric acid. Characterizations were performed on the extracted nanocellulose: thermogravimetric analysis (TGA), ray diffraction (DRX) and scanning electron microscopy (SEM). Based on the TGA results, it is possible to state that cellulose nanofibers (NCFs) were obtained. The presence of cellulose I, cellulose Iᵦ and cellulose II was observed, which is in accordance with the data found in the literature. XRD results demonstrated that the crystallinity of the nanocellulose obtained in this work is similar to the one described in the scientific literature for lignocellulosic fibers, with crystallinity index around 67.03%. From the SEM, it was noted that the nanocellulose obtained has characteristics that may be similar to the spiderweb format. This is characteristic of dispersions that result in nanocellulose gels, specifically cryogels. It is understood that the method of extraction and isolation influence the type of cellulose, as well as the diameter of the nanocellulose.